UTILIZATION OF AFRICAN LEAVES (VERNONIA AMYGDALINA) TO LOWER BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: A SYSTEMATIC REVIEW - Putri, Adira Aulia; Mukaromah, Irdat; Pratiwi, Novi Dwi; Alivian, Galih Noor (International Journal of Biomedical Nursing Review, 2022)
Introduction: Hypertension is a non-communicable disease caused by genetics, stress, and lack of physical activity. So far, no effective drugs have been found to cure high blood pressure. Vernonia amygdalina contains substances that can lower blood pressure, namely flavonoids and potassium. Purpose: The systematic review aims to assess the potential of vernonia amygdalina in lowering blood pressure in hypertensive people. Methods: Articles are obtained from electronic databases such as PubMed, ScienceDirect, and Google Scholar published from 2011 to 2021. Keywords used: ("African leaf" OR "bitter leaf" OR "vernonia amygdalina") AND (hypertension OR "high blood pressure ") NOT" low blood pressure ". Results: The results of the six selected articles indicate that vernonia amygdalina is able to lower blood pressure. This is proved in the hypotensive experiments of cats, suggesting that vernonia amygdalina can affect a significant drop in blood pressure in normotensive cats. Discussion: The flavonoid content of vernonia amygdalina can increase the biogibility of nitrous oxide (NO) and cause vasodilatation and endothelium vasodilation. Potassium may also cause vasorrhea to react through a membrane hyperpolarizing and thus encourage the closing of the calcium channel. Conclusion: It can be determined that vernonia amygdalina's consumption potentially lowers blood pressure in hypertensive people.